2019
DOI: 10.1038/s41598-019-45755-2
|View full text |Cite
|
Sign up to set email alerts
|

Reaching measures and feedback effects in auditory peripersonal space

Abstract: We analyse the effects of exploration feedback on reaching measures of perceived auditory peripersonal space (APS) boundary and the auditory distance perception (ADP) of sound sources located within it. We conducted an experiment in which the participants had to estimate if a sound source was (or not) reachable and to estimate its distance (40 to 150 cm in 5-cm steps) by reaching to a small loudspeaker. The stimulus consisted of a train of three bursts of Gaussian broadband noise. Participants were randomly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 61 publications
4
20
0
Order By: Relevance
“…The authors proposed a model in which, after the feedback session, the participants were able to apply an optimal correction without altering the slope (associated with the response range). Interestingly, when we applied the model proposed by Hüg et al (2019) to our average reaching data, we observed that the blind participants' intercept yielded an almost optimal response (unsigned bias is minimized and signed bias is very close to zero), while sighted participants were far from optimality. That is, blind participants had an average response similar to that reported by Hüg et al (2019) for sighted participants after a feedback session.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The authors proposed a model in which, after the feedback session, the participants were able to apply an optimal correction without altering the slope (associated with the response range). Interestingly, when we applied the model proposed by Hüg et al (2019) to our average reaching data, we observed that the blind participants' intercept yielded an almost optimal response (unsigned bias is minimized and signed bias is very close to zero), while sighted participants were far from optimality. That is, blind participants had an average response similar to that reported by Hüg et al (2019) for sighted participants after a feedback session.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, when we applied the model proposed by Hüg et al (2019) to our average reaching data, we observed that the blind participants' intercept yielded an almost optimal response (unsigned bias is minimized and signed bias is very close to zero), while sighted participants were far from optimality. That is, blind participants had an average response similar to that reported by Hüg et al (2019) for sighted participants after a feedback session. This result suggests that blind participants could be using the audio-motor feedback obtained from manipulating nearby sources to calibrate ADP and that this calibration is kept over time.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…We have performed a study to compare the effect of active and passive exploration on a task where participants, blindfolded and seated, had to reach toward a sound source located in front of them at different distances (similar task as in Hüg et al, 2019). In the active condition, during a training session participants freely explored the arrangement until reaching and touching the sound source.…”
Section: Is There Ever a Purely Passive Or Purely Active Condition?mentioning
confidence: 99%